Tough birds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
You can rear ducks for eggs and meat, use their manure as fertiliser, and sell their down and feathers. Ducks are hardier than chickens and are easier and cheaper to keep though, unlike chickens, they need access to bathing water to be able to breed...